A China and India: On the Edge of Water Disputes and Co-operation - Afzal, Naila; yaseen, zahid; Muhammad Muzaffar, Muhammad Muzaffar (Journal of Arts & Social Sciences, 2020)
This study explores the scarcity of water within two populous states of the world, World has challenge of water war owing the water conflict between the two thirsty nations of the world that might transfer into global war. Qualitative as well as quantitative research methodology was used. Ramification of the study is founded under the current diplomatic and bilateral scenario of the two states, upper riparian states of the region including China and India wanted to divert river water flow to avoid water scarcity in future that might damage agriculture and industry of lower riparian states. It is also recommended that United Nation and other International Organizations should play their part and introduce agreed law and policy of water distribution for the protection of global water conflict.